Fulfill Promises and Avoid Breaches to Retain Satisfied, Committed Nurses. Issue 4 (3rd May 2016) - Rodwell, John; Ellershaw, Julia
Abstract: Purpose: This study examines two commonly proposed mechanisms, violation and trust, to see if they mediate the relationships between the components of the psychological contract (i.e., promises, fulfillment, and breach) and their impact on the work‐related outcomes of job satisfaction, intent to quit, and organizational commitment. Design: Online surveys were completed by 459 Australian nurses. Findings: Structural equation modeling revealed that breach and fulfillment have direct and mediated effects on the outcomes, whereas promises had no impact. Violation partially mediated the relationship between breach and job satisfaction and intent to quit, while trust partially mediated the relationships between fulfillment and organizational commitment, and breach and organizational commitment. Conclusions: Negative experiences (i.e., breaches) were related to both increased feelings of violation and decreased feelings of trust. In contrast, positive experiences (i.e., fulfillment) increased trust but did not significantly reduce feelings of violation. Nurse and organizational managers can use these findings to improve communication with nurses so as to minimize the negative effects of breach and maximize the positive effects of fulfillment and thus improve attitudes. Clinical Relevance: Nurse managers need to be careful to make promises regarding their nurses' employment that they can fulfill and to particularly avoid breaking the psychological contract. The potentially disproportionate negative effect of breach means that a breach can undo a lot of efforts to fulfill employment‐related promises.